Simulation of the Effect of Coal Microstructures on the Macroscopic Mechanical Behavior - Yu Fu; Zhongliang Feng (Advances in Civil Engineering)
This paper investigates the influence of mineral structure on macromechanical behavior of coal under different loading conditions using X-ray CT scanning experimental and numerical methods. The three-dimensional (3D) reconstruction of coal was conducted to assess the spatial distribution characteristics of the mineral structure by AVIZO software. Based on fractal box dimension (BCD) and equivalent diameter, the mineral structures were quantitatively characterized. The 3D finite element models with three distribution characteristics of minerals were built, and the model was considered as a random heterogeneous two-phase material composed of coal matrix and mineral matter. The results show that the frequency of mineral structures decreases with the increase of equivalent diameter in the coal sample. The BCD of the original mineral structure in coal is greater than 2, but the BCD of each part of the minerals divided based on the screening principle is less than 2. Under uniaxial conditions, the elastic modulus, peak strength, and residual strength of coal are monotonically increasing with the size of the mineral structure. The larger the mineral structure size and the more complex the distribution are, the greater the area of stress concentration and the more uniformity the distribution will be. The failure (plasticity) first occurred at the interface between the matrix and the mineral, and the failure zone is significantly different due to the influence of different mineral structures. Under confining pressure, the presence of mineral structure decreases the brittleness of coal, and the variation of brittleness is related to the size and spatial distribution of mineral structures. The fitting relationship between confining pressure and brittleness index is linear, and the correlation coefficient exceeds 0.95.